(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Most children were admitted to the hospital without fever, but even in those cases when the increase in temperature persisted at the time of admission, the main complaint in both groups was cough: in group 1 in 56% and in group 2 in 24% of patients. Frequent wet cough occurred in children with biofeedback 2 times more often than without biofeedback. Dyspnea of a clearly expiratory nature was observed in 40% of the observed children; in the rest it was of a mixed nature, but with a predominance of difficulty in exiting. However, wheezing occurred in all children with bronchial obstruction. Dyspnea was present in 35% of children in group 1. The average duration of dyspnea was 5.25±3.4 days. Impaired nasal breathing was detected in 53.9% of children in group 1. In dynamics, the duration of nasal breathing disturbance was: 6.25±2.9.